Expansión maxilar rápida. Estudio comparativo del potencial de recidiva en ratas después de la aplicación de láser de media potencia en la sutura media palatina. I Parte - Cáceres Zapata, Hugo (2014)
The aim of this study was to evaluate the effect of middle–power–laser irradiation (19 mW wave length and 904 nm) on bone regeneration after rapid midpalatal expansion of the sagital suture in Wistar albino strain rats. Methodology: 10 rats were divided in two groups: in the first group the midpalatal suture was expanded but nonirradiated and the retention period lasted seven days. The second group was treated like the first one but irradiation was applied during 8 minutes per day during the retention period. Rats from both groups were sacrificed in a CO2 chamber for posterior histological examination. Results: Microscopic observation showed significant acceleration on bone regeneration in the irradiation group when compared with the control group. Conclusions: This findings suggest that middle-power-laser irradiation can accelerate bone regeneration in the midpalatal suture after rapid palatal expansion. The mechanism by which laser irradiation promotes bone formation is not fully understood but it probably works by increasing angiogenesis, ATP and collagen synthesis and calcium ions deposits due to modification in the cellular membrane permeability. Bone formation acceleration by laser irradiation could decrease relapse and the retention period after rapid maxillary palatal expansion. This objective was evaluated in the second phase of this study.